1990
DOI: 10.1152/jappl.1990.68.4.1534
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adenosine on cerebral blood flow during hypoxic hypoxia in the newborn piglet

Abstract: This study investigated the role of adenosine in the regulation of neonatal cerebral blood flow (CBF) during moderate (arterial PO2 = 47 +/- 9 Torr) and severe (arterial PO2 = 25 +/- 4 Torr) hypoxia. Twenty-eight anesthetized and ventilated newborn piglets were assigned to four groups: 8 were injected intravenously with the vehicle (controls, group 1); 13 received an intravenous injection of 8-phenyltheophylline (8-PT), a potent adenosine receptor blocker, either 4 mg/kg (group 2, n = 6, mean cerebrospinal flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…4,20,[29][30][31][32][33][34][35][36][37] Animal models have shown a loss of cerebral vascular resistance in the postanoxic state resulting in uncontrolled hyperperfusion. [38][39][40][41][42] Cerebral blood volume has been shown to increase with loss of autoregulation secondary to ischemia, but no large studies have demonstrated a similar relationship for CBF. 43 Relative hyperperfusion has been shown in the thalamus, cerebellum, and occipital lobes with O-15 PET imaging in resuscitated patients; however, this method does not quantitate flow.…”
Section: Resultsmentioning
confidence: 99%
“…4,20,[29][30][31][32][33][34][35][36][37] Animal models have shown a loss of cerebral vascular resistance in the postanoxic state resulting in uncontrolled hyperperfusion. [38][39][40][41][42] Cerebral blood volume has been shown to increase with loss of autoregulation secondary to ischemia, but no large studies have demonstrated a similar relationship for CBF. 43 Relative hyperperfusion has been shown in the thalamus, cerebellum, and occipital lobes with O-15 PET imaging in resuscitated patients; however, this method does not quantitate flow.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that 8-PT had no effect on the sustained ventilatory response to hypoxia in the 3-week-old piglets is perhaps surprising since the concentration of adenosine in the cerebrospinal fluid of 1-month-old piglets has been shown to rise substantially during hypoxia (Pa,o2: 27 mmHg; Laudignon et al 1991). By this age, the stimulatory effect of the peripheral chemoreceptors upon ventilation can apparently overcome the depressive effect of centrally released adenosine, at least during hypoxia lasting 5 min.…”
Section: Responses Evoked In Older Pigletsmentioning
confidence: 99%
“…Brain adenosine levels have been shown to rise in the brain interstitial fluid or cerebrospinal fluid (CSF) soon after the onset of total ischemia and hypoxia (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Adenosine in CSFis thought to be responsible for the cerebral vasodilatation which increases CBF,because a ventriculocisternal perfusion of adenosine causes an increase in CBF (14), and because the instillation of adenosine deaminase or a potent adenosine receptor blocker, 8-phenyltheophylline or theophylline into CSFreduces the hypoxic and hypercapnic dilatation or rat pial arterioles or CBF, respectively (3,15).…”
Section: Introductionmentioning
confidence: 99%